AJARAN MORAL TUAN GURU DAN PENGARUHNYA TERHADAP LAKU KEBERAGAMAAN MASYARAKAT MUSLIM SASAK DALAM PERSPEKTIF ISLAM DAN SOSIOLOGI MODERN - Muhyidin Azmi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2022)
This research departs from an empirical phenomenon that occurs in the social environment of the Sasak people on the island of Lombok, that the Sasak Muslim community in carrying out their daily lives (social and religious) always standardizes what is good and what is bad to them. what Tuan Guru has taught them. For this reason, this research will examine what kind of moral teachings taught by Tuan Guru to the Sasak people and how these moral teachings are used as a philosophy of life for the Sasak people. This research is a qualitative field research (field research) as well as library research (library research) is research that makes books that discuss the themes studied as data sources in research. The object to be studied in this research is Tuan Guru, who is used as a patron in living daily life by the people of Lombok in the social and religious dimensions. As for this study, the authors use the hypothetical structure or theoretical framework of Peter L. Berger's social construction (sociology of knowledge) which will then be used to analyze the social cycle of Tuan Guru and Lombok society in general. As for the results of this study, there are several value systems instilled by Tuan Guru in the Sasak people, namely; faith, piety and social values.